Myelodysplastic syndromes: A primary care perspective - Keshena Naidoo; Sharlene Parasnath (South African Family Practice, 2025)
Myelodysplastic syndromes (MDS) are a group of blood disorders affecting the bone marrow resulting in cytopenia, blood cell dysplasia and an increased risk of progressing to acute myeloid leukaemia (AML). Myelodysplastic syndromes are more common in individuals older than 60 years, and those who have undergone radiation or chemotherapy in the past. Patients may be asymptomatic in the initial stages and can later develop fatigue, dyspnoea, frequent infections, petechiae, bruising and bleeding. Patients with persistent cytopenia (6 months) should be investigated further and referred to a haematologist if at high risk for MDS. The definitive diagnostic test for MDS is a bone marrow biopsy. Individuals with lower-risk MDS can be managed with blood transfusions, erythropoiesis stimulating agents, growth factors and lenalidomide (an immunomodulatory drug). Higher risk MDS patients have a median survival of less than three years, with stem cell transplant as the only cure. However, less than 10% of MDS patients receive this treatment because of the scarcity of donors. Primary care providers should also be aware of long-term side effects following a stem cell transplant. This article aims to increase awareness of MDS and stem cell transplants.